RELATIONSHIP BETWEEN EXECUTIVE MANAGEMENT PRACTICES AND THEIR IMPACT ON THE PERFORMANCE OF STRATEGIC OBJECTIVES - Saad Faysil Mahmoud (Scholar Express Journals, 2025)
This study aims to clarify the impact of Executive Management (EM), on the dimensions of strategic goals (Competition-CO, Innovation-IN, Continuous Improvement- CI). The researcher focused on clarifying the importance of dimensions and variables to raise the efficiency of organizations’ performance. In this study, the researcher focused his work on all the data that was distributed. The number of forms was (100) forms. The valid results were (95) forms and the invalid ones were (5). The target sample was Iraqi Oil Tankers Company. SPSS statistical analysis was used in order to reach positive results SPSS statistical analysis was used to reach positive results and using Likert 7 in the questionnaire. All the results collected about the employees working in the Iraqi Oil Tanker Company were positive. Despite the difficulties faced by the researcher, he was able to reach basic recommendations that institutions need to achieve competition, increase productivity, and expand the role of executive management in influencing the dimensions of strategic objectives.
Keywords: Executive Management; Strategic objectives; Competition